The Kinetics of CD8+ T Lymphocytes in Dengue Patients in Yogyakarta - Loo Huai Na; Umi Solekhah Intansari; Ida Safitri Laksanawati (Pusat Kedokteran Tropis, 2012)
ABSTRACTIntroduction: Dengue fever can be graded into dengue fever (DF), dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). The CD8+ T lymphocytes mediate antiviral activity by producing cytokines and directly destroyed the dengue virus infected cells. This study focuses in observing the kinetics of CD8+ T lymphocytes absolute and relative count in dengue patients.Objectives: To observe the kinetics of CD8+ T lymphocytes absolute and relative count in dengue patients.Methods: The research design used is a descriptive study. This research measures and observes the kinetics CD8+ T lymphocytes absolute and relative count from day 2 to day 7. The CD8+ T lymphocytes count was determined using flowcytometry. Data was analyzed using ANOVA and independent t test with p<0.05 considered as significant.Results: The CD8+ T lymphocytes absolute count is low during the beginning of disease course and it gradually increases from day 2 to day 7. The CD8+ T lymphocytes relative count decreases from day 2 to day 3, and start to increase back from day 3 to day 7. There is no difference between the level of CD8+ T lymphocytes absolute count and relative count between DF and DHF patients.Conclusion: There is an increase in CD8+ T lymphocytes absolute count and relative count in dengue patients. There is no difference between DF and DHF patients in CD8+ T lymphocytes absolute and relative count. Keywords: dengue fever; dengue hemorrhagic fever; CD8+ T lymphocytes; absolute count; relative count.